KINERJA KEUANGAN PERUSAHAAN TRANSPORTASI BERBASIS LAPORAN KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yuniastuti, Rina Milyati; Nasyaroeka, Jhon (Jurnal Manajemen Magister Darmajaya, 2017)
The financial performance of transportation companies in Indonesia stock exchange gives long term contribution in providing information and decision of the company perfomance. Transportation company can attract investors because of its performance. The method used is the that is research that uses data collection methods by looking at the financial statements that exist in the stock exchange indonesia.From the financial statements can be seen transportation through ratio ratio of liquidity ,ratio solvability, and ratio prifitability .Result of the research that for the ratio of liquidity andÂ  ratioÂ  profitability of financial performance in good condition,while at the ratio solvability financial performance in the condition of the most value ratio of the company decreased.Keyword: Performance, Ratio Liquidity, Ratio Solvability, Ratio Profitability, Financial Report